2022
DOI: 10.3390/antiox11050807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alga Gelidium sp. Flour Extract on Lipid Damage Evolution in Heated Fish Muscle System

Abstract: This research aimed to evaluate the antioxidant properties of flour obtained from red alga Gelidium sp., which is underutilised nowadays in food applications. Thus, a model system consisting of minced mackerel (Scomber scombrus) muscle and aqueous flour extract was subjected to heating treatment (50 °C) for 11 days. Resulting levels on conjugated diene (CD) and triene (CT) contents, peroxide value, thiobarbituric acid index, and fluorescent compound and free fatty acid (FFA) formation were monitored at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Furthermore, aqueous extracts obtained from other marine substrates have also exhibited valuable antioxidant properties during seafood processing. In studies of brown [12,30], green [12], and red [13] macroalgae, proteins, peptides, and especially polysaccharides were reported to be responsible for antioxidant behaviour. Additionally, the use of water instead of organic solvents is currently recommended because it is considered an ecofriendly procedure.…”
Section: Raw Fish Starting Ink and Preparation Of The Ink Extractmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, aqueous extracts obtained from other marine substrates have also exhibited valuable antioxidant properties during seafood processing. In studies of brown [12,30], green [12], and red [13] macroalgae, proteins, peptides, and especially polysaccharides were reported to be responsible for antioxidant behaviour. Additionally, the use of water instead of organic solvents is currently recommended because it is considered an ecofriendly procedure.…”
Section: Raw Fish Starting Ink and Preparation Of The Ink Extractmentioning
confidence: 99%
“…Most research regarding heat-treated seafood has shown low values for primary lipid oxidation compounds, indicating a marked effect of the thermal breakdown on primary compounds. Such research has concerned heated-minced mackerel (Scomber scombrus) (50 • C for 11 days) (low CD, CT, and peroxide contents) [13] and different kinds of canned seafood like bluefin tuna (Thunnus thynnus) and sardine (Sardina pilchardus) (low peroxide content) [42], Atlantic mackerel (S. scombrus) (low CD, CT, and peroxide contents) [30], Atlantic Chub mackerel (Scomber colias) (low peroxide content) [12], and eel (Anguilla anguilla) (low peroxide content) [48]. However, and according to the present results, a relevant increase in the primary compound contents has been detected in a heated marine oil system (increase in peroxide content) [11] and in cooked salmon (increase in peroxide content) (Salmo salar) pasta [49].…”
Section: Lipid Oxidation Development In the Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The protective effect of flour from Gelidium sp. on the nutritional and sensorial values of thermally treated seafood was monitored and assessed [ 25 ]. Other hydrocolloid-based foods, such as surimi protein gel, together with their additives, were also studied in terms of retarding protein oxidation and denaturation.…”
Section: Technological Advances In the Incorporation Of Natural Antio...mentioning
confidence: 99%